Improvement of stress tolerance in plants by genetic manipulation of mitogen-activated protein kinases - Šamajová, Olga; Plíhal, Ondřej; Al-Yousif, Mohamed; Hirt, Heribert; Šamaj, Jozef (Biotechnology advances, 2013)
Plant stress tolerance depends on many factors among which signaling by mitogen-activated protein-kinase (MAPK) modules plays a crucial role. Reversible phosphorylation of MAPKs, their upstream activators and downstream targets such as transcription factors can trigger a myriad of transcriptomic, cellular and physiological responses. Genetic manipulation of abundance and/or activity of some of these modular MAPK components can lead to better stress tolerance in Arabidopsis and crop plant species such as tobacco and cereals. The main focus of this review is devoted to the MAPK-related signaling components which show the most promising biotechnological potential. Additionally, recent studies identified MAPK components to be involved both in plant development as well as in stress responses, suggesting that these processes are tightly linked in plants.
Keywords: Mitogen-Activated Protein Kinases; Plant Growth Regulators; geneticky modifikované rostliny; Stress, Physiological; mitogenem aktivované proteinkinasy; Arabidopsis; fyziologický stres; Genetic Engineering; Phosphorylation; Crops, Agricultural; regulátory růstu rostlin; genetické inženýrství; Plants, Genetically Modified; fosforylace; Plant Physiological Phenomena; fyziologie rostlin; zemědělské plodiny